NANOCRYSTALS: A TOOL FOR ENHANCING DRUG DISSOLUTION - Sadhu Venkateswara Rao; Gopu Navyatha; Parakat Tanmai Meenakshi; Akunuri Sai Divya; Chandolu Lakshmi Akhila Jahnavi; Kantamneni Padmalatha (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Poor aqueous solubility is a significant challenge in the formulation and delivery of many pharmaceutical compounds, leading to suboptimal bioavailability and therapeutic efficacy. Nanocrystals have emerged as a promising approach to address this issue by enhancing drug dissolution and improving drug delivery systems. This review provides an in-depth analysis of the role of nanocrystals in enhancing drug dissolution and their potential as a tool for improving drug formulations and explaining the principles of nanocrystal technology, including the media milling, preparation method and homogenization method, and the use of stabilizers and surfactants to prevent aggregation. The applications of nanocrystals in different drug delivery systems are explored, including oral, parenteral, and topical routes. In conclusion, nanocrystals represent a powerful tool for enhancing drug dissolution and improving drug delivery systems for poorly water-soluble drugs. Their ability to enhance bioavailability and therapeutic efficacy holds great promise for advancing pharmaceutical development.